2020
DOI: 10.1002/cbf.3455
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor class A, member 5 is associated with thyroid cancer cell lines progression via epithelial‐mesenchymal transition

Abstract: Thyroid cancer (TC) has become one of most common endocrine malignancies in recent decades. Due to gene background polymorphism, it's outcome goes quite differently in each patient. For exploring the mechanism, we performed whole transcriptome sequencing of paired papillary thyroid carcinoma (PTC) and adjacent thyroid tissues. As a result, scavenger receptor class A member 5 (SCARA5) might be a crucial anti-oncogene associated with PTC. By RT-qPCR, we first detected the expression of SCARA5 in PTC tissue and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…SLC5A8 codes for a transporter belonging to the Na(+)/glucose co-transporter gene family, and the protein coded by SLC5A8 can transport iodide and regulate the Na(+)-coupled and electrogenic transport of many monocarboxylates ( 39 ). Our results support our earlier observations, which showed that SEMA3D ( 40 ), CRABP1 ( 41 ), SLC5A8 ( 42 ), and SCARA5 ( 43 ) are tumor suppressor genes in PTC, while GDF15 ( 44 ), CHI3L1 ( 45 , 46 ), GABRB2 ( 47 ), and ARHGAP36 ( 48 ) are oncogenic genes in PTC. However, very little research has been conducted on the roles of B3GNT3 , TMPRSS6 , CLDN16 , MFAP4 , MYOC , C7 , APOD , SLIT1 , TMEM215 , and IGSF1 in PTC.…”
Section: Discussionsupporting
confidence: 92%
“…SLC5A8 codes for a transporter belonging to the Na(+)/glucose co-transporter gene family, and the protein coded by SLC5A8 can transport iodide and regulate the Na(+)-coupled and electrogenic transport of many monocarboxylates ( 39 ). Our results support our earlier observations, which showed that SEMA3D ( 40 ), CRABP1 ( 41 ), SLC5A8 ( 42 ), and SCARA5 ( 43 ) are tumor suppressor genes in PTC, while GDF15 ( 44 ), CHI3L1 ( 45 , 46 ), GABRB2 ( 47 ), and ARHGAP36 ( 48 ) are oncogenic genes in PTC. However, very little research has been conducted on the roles of B3GNT3 , TMPRSS6 , CLDN16 , MFAP4 , MYOC , C7 , APOD , SLIT1 , TMEM215 , and IGSF1 in PTC.…”
Section: Discussionsupporting
confidence: 92%
“…SCARA5 downregulation was essential for EMT-induced migration in A549 cells and SCARA5 was a direct Snail1 target modulating cancer cell mobility during EMT 8 . SCARA5 also modulated the expression of epithelial-mesenchymal transition-related proteins in thyroid cancer 18 . These results demonstrated that SCARA5 could inhibit cell invasion and metastasis by modulating the actin cytoskeleton in cancer cell lines.…”
Section: Discussionmentioning
confidence: 94%
“…Meanwhile, Liu et al found that CNS5 and SPAG5 could affect hepatocellular carcinoma progression by mediating ubiquitination of β-catenin to reduce the expression of SCARA5 [ 9 , 10 ]. Moreover, Chen and Liu et al also discovered that the aberrant expression of SCARA5 in thyroid cancer and lung cancer impacts cellular invasion and migration [ 11 , 12 ]. What’s more, Li et al reported that SCARA5 could act as ferritin receptor to facilitate intracellular iron increasing and promote the kidney development [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other family members that are found primarily in macrophages, scavenger receptor protein 5 (SCARA5), located on chromosome 8p21, is widely expressed in a variety of human tissues, including bladder, ovary, kidney, and skin [7]. SCARA5 has been reported to act as a tumor suppressor in many cancers [6,[8][9][10][11][12]. For example, Huang and Ulker et al respectively reported that the expression of SCARA5 was specifically decreased in hepatocellular carcinoma and breast cancer due to promoter methylation [6,8].…”
Section: Introductionmentioning
confidence: 99%